The Effect of Interferon-Inducible T Cell Alpha Chemoattractant (I-TAC) on Transplanted Mice with Breast Cancer - Hind Mohammed; Arwa Al-Shuwaikh; Ahmed Al-Shammari (The Iraqi Journal of Medical Sciences)
Background: Interferon-inducible T-cell alpha chemoattractant (I-TAC, CXCL11) is a novel chemokine that used as immunotherapy. CXCL11 develops an effective anti-tumor immune response that relies on the coordinated interactions between immunocompetent cells, suppress angiogenesis and leading to an anti-tumor effect. Objective: To investigate the anti-tumor effect of CXCL11 on breast cancer transplanted in an animal’s model. Methods: CXCL11 adoptive immunotherapy inducible, was intratumorally injected in mice breast cancer model one dose weekly for three weeks, each dose concentration 20 ng/100μl. Weight of mouse and size of tumor were recorded every 48 hr until 25 days. Parameters examined on mice transplanted with murine mammary adenocarcinoma (AMN3) cells (to study the therapeutic of CXCL11 in vivo) were included growth inhibition (GI%), relative tumor volume (RTV), relative mice weight (RMW) and survival time in mice. Results: In-vivo CXCL11 treatment showed to induce GI% from day 3 and continued to day 25 with significant increase in mice weight in comparison to non-treated control group during 25 days (P<0.0001). Also, the CXCL11 treatment exhibited a significant reduction in RTV and improving survival time in mice. Conclusion: CXCL11 showed an anti-cancer effect on breast cancer AMN3 implanted in mice compared to control. CXCL11 may have immunotherapeutic effect on breast cancer by triggering the activation of immunity against cancer. Keywords: Breast cancer, CXCL11, immunotherapy, AMN3 Citation: Mohammed HA, Al-Shuwaikh AM, Al-Shammari AM. The effect of interferon-inducible T cell alpha chemoattractant (I-TAC) on transplanted mice with breast cancer. Iraqi JMS. 2023; 21(1): 81-87. doi: 10.22578/IJMS.21.1.8